Características gramaticais do Guarani Mbya da Costa Verde do Estado do Rio de Janeiro - Mello, Alexandre Raymundo de (2023)
This dissertation aims at exposing the differences and grammatical characteristics of the Mbya Guarani language spoken by the Guarani from the so called Costa Verde region in the State of Rio de Janeiro, Brazil. Our study is based first and foremost on the variety of Mbya Guarani spoken in the villages of Sapukai (Bracuí, municipality of Angra dos Reis) and Itaxi (Paraty Mirim, municipality of Paraty). We compared the variety of Mbya Guarani spoken in the villages located in those two municipalities with the varieties spoken in the southern region of Brazil and neighboring areas of the triple frontier of Brazil, Argentina and Paraguay. For the varieties of the language spoken in the southern region of Brazil and in the triple frontier region, our study conducted a secondary research based on data acquired from the works of Tibiriçá (1989), Dooley (1998, 2006) and Cecy Fernandes de Assis (2008). For the variety of the language spoken on the Costa Verde of the State of Rio de Janeiro, our study conducted a primary research via unstructured interviews and conversations with several speakers of the language. One other source of information used in this study was the comparison between the vast amount of text produced in the Guarani language and the texts produced by Guarani speakers from various regions. In order to write this dissertation, we felt the need to understand the historical origins of the Mbya Guarani speakers, as well as the history of the families in this research, including their geographic origin, their social and cultural relations, their position in the political hierarchy of the villages, and their religious values. It was also necessary to analyze the routes taken by the families when moving across the Costa Verde region, as well as their bonds of kinship. The comparison between the grammatical characteristics of the Mbya Guarani spoken in the Costa Verde region and the one spoken in the other regions has led us to infer that, in the former variety, there is a tendency for structural simplification based on the communication context. That is to say that certain structures remain implicit because their meanings are deduced from the communication situation. The choice of one structure over one other may affect the constituent order of a clause and its prosodic structure.